Pengaruh Group Cognitive Behavioral Therapy untuk Menurunkan Kecemasan pada Wanita Infertilitas Primer - Dian Syafitrah; Rahma Widyana; Siti Noor Fatmah L (Jurnal Psikologi, 2019)
This study aims to determine effect of Group Cognitive Behavioral Therapy to reduce anxiety women in Primary infertility. The program given refers to the theory compiled by Folger & Edward (2008), namely Sharing, Relaxation, Psychoeducation, Cognitive restructuring, Problem solving, Self-monitoring, and Activity scheduling. The study participants were 6 people with high anxiety level, based on Taylor Manifest Anxiety Scale (TMAS) score. The statistical method used to analyze the data is the Wilcoxon method. The results showed a decrease in anxiety levels after treatment (Z = -2.201, p <0.05).   This means that there is an effect of Group Cognitive Behavioral Therapy on the decrease of anxiety women in primary infertility, before the mean therapy 34.00 and after the treatment of the mean of 12.33. Therefore it can be inferred that the research hypothesis is accepted, there is decreased anxiety after the Group Cognitive Behavioral Therapy. Keywords: Anxiety, Group Cognitive Behavioral Therapy (Group CBT).